2023
DOI: 10.4081/ripppo.2023.693
|View full text |Cite
|
Sign up to set email alerts
|

Problematic internet use in emerging adulthood to escape from maternal helicopter parenting: defensive functioning as a mediating mechanism

Nicola Carone,
Ilaria Maria Antonietta Benzi,
Laura Muzi
et al.

Abstract: The increasing use of the Internet has raised concerns about its problematic use, particularly among emerging adults who grew up in a highly digitalized world. Helicopter parenting, characterized by excessive involvement, overcontrol, and developmentally inappropriate behavior, has been identified as a potential factor contributing to problematic Internet use (PIU). Under these circumstances, considering that emerging adults navigate their adult lives and strive to reduce their sense of being in-between, impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Defense mechanisms, as studied in clinical and non-clinical contexts (Carone et al ., 2023a ; 2023b ; Cramer, 2007; Perry & Bond, 2012 ), offer insights into psychological functioning. Identifying defense mechanisms and defense profiles in clinical settings is helpful for successful treatment outcomes (Perry & Bond, 2012 ; Cramer, 2007; Perry et al ., 2019 ), and improvement in defensive functioning has been linked to improved psychological functioning in general as well as better treatment outcomes (Kramer et al ., 2013; Perry, Knoll, & Tran, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Defense mechanisms, as studied in clinical and non-clinical contexts (Carone et al ., 2023a ; 2023b ; Cramer, 2007; Perry & Bond, 2012 ), offer insights into psychological functioning. Identifying defense mechanisms and defense profiles in clinical settings is helpful for successful treatment outcomes (Perry & Bond, 2012 ; Cramer, 2007; Perry et al ., 2019 ), and improvement in defensive functioning has been linked to improved psychological functioning in general as well as better treatment outcomes (Kramer et al ., 2013; Perry, Knoll, & Tran, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature has applied the DMRS in research and has demonstrated that defense mechanisms are strongly related to mental health ( Perry and Cooper, 1989 ; Perry and Bond, 2012 ; Di Giuseppe et al, 2022 ; Perry et al, 2022 ; Carlucci et al, 2023 ). Mature defensive functioning is associated with better personality functioning and fewer symptoms ( Giovanardi et al, 2021 ; Tanzilli et al, 2022 ; Conversano et al, 2023 ; Martino et al, 2023 ; Messina et al, 2023 ), while immature defensive functioning is related to psychopathology ( Perry and Cooper, 1989 ; Babl et al, 2019 ; Boldrini et al, 2020 ; Conversano et al, 2020 ; Carone et al, 2023 ; Vierl et al, 2023 ). Severe personality disorders are associated with low defensive functioning, action defenses, and major image-distorting defenses, which predict depression, suicidal attempts, substance use, and self-harming behavior ( Perry and Cooper, 1989 ; Perry et al, 2020 ; Fiorentino et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%